Post Occupancy Evaluation of the Library Building: Diyarbakir Prof. Dr. Fuat Sezgin Provincial Public Library - DEMİR KAYAN Hale; ERGÜN Ruşen (Architecture, Civil Engineering, Environment)
Libraries are one of the oldest public buildings in history. Their main goal is to provide access to and disseminate information. There are various types of libraries according to user profile and purposes such as university libraries, school libraries, national libraries, and public libraries. Public libraries have the most comprehensive library feature, serving all people for free. It is also a place for people’s socialization and cultural activity. This study aims to evaluate the building performance of Diyarbakır Professor Doctor Fuat Sezgin Provincial Public Library. In the study, Post-Occupancy Evaluation method was used. The results were made about the design quality, indoor environment quality and service quality. The satisfaction index formula developed by Dominowski was used to analyse user satisfaction. The satisfaction level of design quality was determined as 69.38%, indoor environment quality satisfaction level of 72.79% and service quality satisfaction level as 68.48%. These results show that user satisfaction generally remains at a negative level. In this study, suggestions have been developed for increasing the satisfaction level of this library building and for new library building designs. It is thought that this study will be a guide to improving the quality of library buildings.